Aplikasi Modified-Imperialist-Competitive-Algorithm (MICA) Untuk Merekonfigurasi Jaringan Radial Tenaga Listrik Pada Penyulang Mojoagung - Machrus Ali; Dwi Ajiatmo; Muhammad Ruswandi Djalal (Muhammadiyah University, Sidoarjo, 2017)
The reconfiguration distribution network is used to reset the network configuration form by opening and closing switches on the distribution network. Reconfiguration is expected to reduce power losses and improve distribution system reliability. Many feeders and buses on the network if calculated manually will be difficult and require a very long time. So the solution of the problem must use artificial intelligence or Artificial Intelligent (AI). Imperialist Competitive Algorithm (ICA) widely used research in solving the optimization problem. Some studies comparing ICA with other artificial intelligence and ICA produce better results than other artificial intelligence. MICA is an ICA modification designed to solve a discrete combination of optimizations. MICA can find the best network reconfiguration so that it can reduce power loss by 35,7928% and fix voltage 0,0185 pu. This method can later use other artificial intelligence or can be applied to other repeater. So it can be used for recommendations to PT. PLN (Persero)